Insertion of screw implant into the jaw in the 1930s at the Surgical Clinic in Debrecen - Barna Kelentey; Levente Lukács; Pál Redl; Csaba Hegedűs (Hungarian Dental Association, 2018)
The usage of dental implants in the last 30-40 years has significantly altered the potentials in the field of prosthetics. The first evidence of implantation comes from the Mayan culture (around 600 BC). In Europe various techniques and materials were used for implantation purposes between the 16th and 19th centuries. In Hungary it was in 1934 when the first screw implants were placed in the lower jaw, in Debrecen, which was almost immediately supplemented by a bridge restoration. The surgeries were performed by Tivadar Hüttl, professor of surgery and Ágoston Karácsony, dentist. The procedure was applied in several cases, for which they planned to submit a demand for patent protection. However, in the spring of 1935, their patent claim was withdrawn due to a pleading of a licensed dentist in Budapest. We do not know the exact number of inserted implants, or the rate of success, however, their durability is supported by the fact, that there was a patient treated in 1959, who still used such fixed prosthesis. Based on the above case a scientific article was published with photographs and x-rays. Our article briefly reviews the process, its tools, and the controversies surrounding the patenting.